Association of Triglyceride-Related Genetic Variants With Mitral Annular Calcification - Afshar, Mehdi; Luk, Kevin; Do, Ron; Dufresne, Line; Owens, David S; Harris, Tamara B; Peloso, Gina M; Kerr, Kathleen F; Wong, Quenna; Smith, Albert V; Budoff, Mathew J; Rotter, Jerome I; et al. (Journal of the American College of Cardiology, 2017)
Mitral annular calcium (MAC), commonly identified by cardiac imaging, is associated with cardiovascular events and predisposes to the development of clinically important mitral valve regurgitation and mitral valve stenosis. However, its biological determinants remain largely unknown. The authors sought to evaluate whether a genetic predisposition to elevations in plasma lipids is associated with the presence of MAC. The authors used 3 separate Mendelian randomization techniques to evaluate the associations of lipid genetic risk scores (GRS) with MAC in 3 large patient cohorts: the Framingham Health Study, MESA (Multiethnic European Study of Atherosclerosis), and the AGE-RS (Age, Gene/Environment Susceptibility-Reykjavik Study). The authors provided cross-ethnicity replication in the MESA Hispanic-American participants. MAC was present in 1,149 participants (20.4%). In pooled analyses across all 3 cohorts, a triglyceride GRS was significantly associated with the presence of MAC (odds ratio [OR] per triglyceride GRS unit: 1.73; 95% confidence interval [CI]: 1.24 to 2.41; p = 0.0013). Neither low- nor high-density lipoprotein cholesterol GRS was significantly associated with MAC. Results were consistent in cross-ethnicity analyses among the MESA Hispanic-Americans cohort (OR per triglyceride GRS unit: 2.04; 95% CI: 1.03 to 4.03; p = 0.04). In joint meta-analysis across all included cohorts, the triglyceride GRS was associated with MAC (OR per triglyceride GRS unit: 1.79; 95% CI: 1.32 to 2.41; p = 0.0001). The results were robust to several sensitivity analyses that limit both known and unknown forms of genetic pleiotropy. Genetic predisposition to elevated triglyceride levels was associated with the presence of MAC, a risk factor for clinically significant mitral valve disease, suggesting a causal association. Whether reducing triglyceride levels can lower the incidence of clinically significant mitral valve disease requires further study.